Co-Opting Precariousness: Can Worker Cooperatives Be Alternatives to Precarious Employment for Marginalized Populations? A Case Study of Immigrant and Refugee Worker Cooperatives in Canada - Wilson, Amanda (Just Labour, 2010)
This article seeks to analyze whether, or to what degree, worker cooperatives are providing immigrant and refugee populations in Canada with a viable alternative to precarious employment, and if so, in what ways. Much of the existing research on precarious employment is limited in that it fails to address the root causes of precarious employments and fails to offer solutions or alternatives that can be organized by workers themselves, today. While several challenges remain to organizing and sustaining worker cooperatives, the cooperatives studied were successful in creating an alternative space of employment that provided control and flexibility over their work and lives and a sense of community and empowerment. More research is needed to better support and facilitate the development of cooperatives to truly harness the potential for the model.